Stunting pada Anak dengan Tuberkulosis Paru dan Anemia Defisiensi Besi: Laporan Kasus - Putri, Asterisa Retno; Arumndari, Runi; Liman, Claudia Natasha; Dewi, Made Ratna (PT Kalbe Farma Tbk., 2025)
Background: Stunting is defined as low height-for-age caused by chronic or recurrent undernutrition. Undernutrition is the leading risk factor for tuberculosis (TB) globally. It is usually associated with poverty, poor maternal health and nutrition, frequent illness and/or inappropriate feeding and care in early life. Stunting prevents children from reaching their physical and cognitive potential, so appropriate management is needed. Case: weight for age but severely stunted and suggestive TB. Blood study result showed anemia with Mentzer index >13. Bone age showed the age of A 4 year-old girl was referred with breathing difficulty since 2 weeks accompanied with decreased appetite and weight. She was in normal 3 years and below chronological age. Management was focused on TB, nutritional, and anemia treatment. Conclusion: Nutritional assessment should be integrated into standard TB care and also simultaneously treat iron deficiency anemia.